2010
DOI: 10.1007/s10571-010-9546-4
|View full text |Cite
|
Sign up to set email alerts
|

3-Mercaptopropionic Acid-Induced Seizures Decrease NR2B Expression in Purkinje Cells: Cyclopentyladenosine Effect

Abstract: Inhibitory mechanism of cerebellum epileptic activity can be involved depending on the intensity and frequency of seizure convulsions. N-methyl-D-aspartate receptors (NMDARs) play key roles in excitatory synaptic transmission and have been implicated in neurological disorders: in cerebellum, they have specific characteristics. NMDARs are heteromeric complexes, and the expression of functional receptors in mammalian cells requires the subunit NR1 (essential) and one NR2 subtype of the four isoforms: NR2A-NR2D. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Contradictory data about NMDAR subunit expression were obtained in other experimental models. A significant reduction in the production of the GluN2B subunit in various regions of the hippocampus and cerebellum and an increase in the expression of the GluN2A subunit are revealed after repetitive seizures, induced by repeated administration (4–7 days) of convulsant drug 3-mercaptopropionic acid (Auzmendi et al, 2009 ; Girardi et al, 2010 ; Gori and Girardi, 2013 ). A significant increase of GluN2A, but not of GluN2B expression in the immunohistochemical analysis was obtained after repeated epileptic seizures induced for 12 days by intraperitoneal administration of 4-aminopyridine (Borbely et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Contradictory data about NMDAR subunit expression were obtained in other experimental models. A significant reduction in the production of the GluN2B subunit in various regions of the hippocampus and cerebellum and an increase in the expression of the GluN2A subunit are revealed after repetitive seizures, induced by repeated administration (4–7 days) of convulsant drug 3-mercaptopropionic acid (Auzmendi et al, 2009 ; Girardi et al, 2010 ; Gori and Girardi, 2013 ). A significant increase of GluN2A, but not of GluN2B expression in the immunohistochemical analysis was obtained after repeated epileptic seizures induced for 12 days by intraperitoneal administration of 4-aminopyridine (Borbely et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our work, the studied area has been the hippocampus, rich in A 1 R, and its activation by CPA inhibits the release of EAAs and hyperpolarizes the postsynaptic membrane. Girardi et al (2010) have also observed the protective effect of CPA on cerebellar GluN2B expression, an area with high expression of A 1 Rs. These results suggest that CPA would act as a protective agent to reverse the effects of MP toward control conditions acting on A 1 Rs signaling pathways (Milton et al 2008;Nayak et al 2011).…”
Section: Discussionmentioning
confidence: 70%
“…As with neurotransmission per se , much evidence from animal research shows that this effect is A 1 R-mediated. Systemic injection of A 1 R-selective agonists limits seizures and convulsions in numerous types of experimental seizures and epilepsies (Girardi, Auzmendi, Charo, Gori, & Castro, 2010; Girardi, Canitrot, Antonelli, Gonzalez, & Coirini, 2007; Gouder, Fritschy, & Boison, 2003; Li, Kang, Shi, Liu, & Zhang, 2013; Li & Zhang, 2011; Luszczki, Kozicka, Swiader, & Czuczwar, 2005; Mares, 2010; Moezi, Akbarian, Niknahad, & Shafaroodi, 2013; Muzzi, Coppi, Pugliese, & Chiarugi, 2013; Pometlova, Kubova, & Mares, 2010; Tosh et al, 2012; Vianna, Ferreira, Doná, Cavalheiro, & da Silva Fernandes, 2005; Zuchora, Wielosz, & Urbanska, 2005). In addition, A 1 R activation augments the effects of standard AEDs (Borowicz, Łuszczki, & Czuczwar, 2002; Luszczki et al, 2005).…”
Section: Adenosine Receptor Subtypes and Epilepsymentioning
confidence: 99%